Materialized Wishes: Long Banner Paintings from the Mogao Caves of Dunhuang - Hwang, Yoonah (Religions, 2023)
This paper explores the religious function and meaning of long banner paintings from Cave 17 of the Mogao Caves in Dunhuang, in conjunction with material culture in Northwestern China in the ninth and tenth centuries CE. The so-called forty-nine-chi banners have peculiar traits such as extremely long lengths, an optional triangular headpiece, and a paired or single strip of textile on which a series of standing bodhisattvas are painted. The author focuses on the large number of textiles used for such banners and questions how the extraordinary length and material used contributed to fulfilling the donor’s wishes. By examining both the banners’ physical characteristics, such as the type of textiles, pigments, and configurations, and the theological background based on the Buddhist and Daoist scriptures about longevity, repentance, and healing, the author suggests that the long banners are a materialized form of longevity and prosperity by physically lengthening the banner with multiple bolts of silk. This paper further argues that depicting multiple bodhisattvas in a pictorial form on a long strip of textile was regarded equally as a powerful means for obtaining good health, prolonging life, eliminating sins, and thus being reborn in the Pure Land.